Acute TBK1/IKK-ε Inhibition Enhances the Generation of Disease-Associated Microglia-Like Phenotype Upon Cortical Stab-Wound Injury - Rehman, Rida; Tar, Lilla; Olamide, Adeyemi Jubril; Li, Zhenghui; Kassubek, Jan; Böckers, Tobias; Weishaupt, Jochen; Ludolph, Albert; Wiesner, Diana; Roselli, Francesco (Frontiers in Aging Neuroscience, 2021)
Traumatic brain injury has a poorer prognosis in elderly patients, possibly because of the enhanced inflammatory response characteristic of advanced age, known as “inflammaging.” Recently, reduced activation of the TANK-Binding-Kinase 1 (Tbk1) pathway has been linked to age-associated neurodegeneration and neuroinflammation. Here we investigated how the blockade of Tbk1 and of the closely related IKK-ε by the small molecule Amlexanox could modify the microglial and immune response to cortical stab-wound injury in mice. We demonstrated that Tbk1/IKK-ε inhibition resulted in a massive expansion of microglial cells characterized by the TMEM119+/CD11c+ phenotype, expressing high levels of CD68 and CD317, and with the upregulation of Cst7a, Prgn and Ccl4 and the decrease in the expression levels of Tmem119 itself and P2yr12, thus a profile close to Disease-Associated Microglia (DAM, a subset of reactive microglia abundant in Alzheimer’s Disease and other neurodegenerative conditions). Furthermore, Tbk1/IKK-ε inhibition increased the infiltration of CD3+ lymphocytes, CD169+ macrophages and CD11c+/CD169+ cells. The enhanced immune response was associated with increased expression of Il-33, Ifn-g, Il-17, and Il-19. This upsurge in the response to the stab wound was associated with the expanded astroglial scars and increased deposition of chondroitin-sulfate proteoglycans at 7 days post injury. Thus, Tbk1/IKK-ε blockade results in a massive expansion of microglial cells with a phenotype resembling DAM and with the substantial enhancement of neuroinflammatory responses. In this context, the induction of DAM is associated with a detrimental outcome such as larger injury-related glial scars. Thus, the Tbk1/IKK-ε pathway is critical to repress neuroinflammation upon stab-wound injury and Tbk1/IKK-ε inhibitors may provide an innovative approach to investigate the consequences of DAM induction.